Channel modelling and analysis of Wits mock-mine with different antenna parameters - Hussain, Intikhab (My University, 2017)
In the mining industry, communications systems are important for ensuring personnel safety and optimizing the mining processes underground. Achieving robust and reliable through-the-air (TTA) communication systems has always been a challenge in the underground mining environment due to harsh and dynamic conditions. TTA requires radio channel characterization for efficient designing and deploying of the communications systems. The literature covers the statistical radio propagation of a room and pillar coal mine, a longwall coal mine, CANMET Gold mine, Camborne School of Mines hard rock mine tunnel, MUZ Coal mine, an iron-ore mine and a lead-zinc mine with linearly polarized antennas at different frequencies. [Abbreviated Abstract. Open document to view full version]
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2017
Keywords: Mine communication systems--Equipment and supplies; Wireless communication systems; Antennas (Electronics); Radio wave propagation; Mine rescue work--Equipment and supplies